Estudo sobre riscos ocupacionais, biológicos e químicos, em laboratórios de uma universidade pública brasileira, 2012-2013 - Monica Maria Campolina Teixeira Stehling (2013)
Observational, transversal, analytic, qualitative and quantitative study. The community target of our research was composed by researchers, teachers, graduation students, post-graduation students, internships and employees. On the first stage of the thesis we intended to check the factor related to the occurrence of accidents, through a survey about occupational risks, biological and chemical, questioning about Personal Protection Equipment, Biosecurity Handbooks, Customer Service to the Victims and the Standard Operational Procedure. We tried to identify the victims through these risks in three Universidade Federal de Minas Gerais units, the Veterinary College, Odontology College and Medicine College, and the health effects caused by the accidents, using structured and semi-structured questionnaires. Obtained data was organized using Epi-Data 3.1® software. The statistics analysis was done using Stata 12.0® software. We used the frequency and proportion method and after it we did selection procedures for the characteristics potentially associated to the occurrence of accidents using univariate statistics tests. Here in after we checked the risk and protection factors to the occurrence of accidents using Multivariate Logistics Regression models. On the second stage of the thesis Focal Groups of victims in the three researched units were made, looking forward to apply the qualitative content analysis method which allows a better exploration, the generation of new concepts and the deep analysis of an idea. We had a 271 individuals sample and we could conclude these individuals are highly exposed to the risks studied (from 70.5% to 97.3%) with a significant amount of victims (48.0% at the Veterinary College, 34.4% at the Odontology College and 23.0% at the Medicine College). Besides that, along with these results, we could perceive a need of behavior changes, continuous and systematized information and the implantation of programs which aim the vigilance when it comes to workers health in the ambit of UFMG.